New simple and quick method to analyze serum variant transthyretins: direct MALDI method for the screening of hereditary transthyretin amyloidosis - Toshiya Nomura (Orphanet Journal of Rare Diseases, 2019)
Abstract Background Hereditary transthyretin amyloidosis (ATTRv amyloidosis) is caused by a variant transthyretin (TTR), which is a serum protein secreted by the liver. Mass spectrometry (MS) is a useful tool that can detect variant TTRs in serum samples from patients with ATTRv amyloidosis. We previously reported several mass spectrometric methods to detect variant TTRs in serum samples. Those methods require cumbersome immunoprecipitation with anti-TTR antibodies and significant time to analyze the variant TTRs. In our study here, we developed a new simple and quick method to detect variant TTRs in serum samples by means of matrix-assisted laser desorption-ionization time-of-flight (MALDI-TOF) MS without immunoprecipitation (direct MALDI). Methods By using direct MALDI, we analyzed 288 serum samples obtained from patients who were clinically suspected having amyloidosis to investigate the usefulness of this direct MALDI method to detect variant TTRs in serum samples. Results The method completed the process within 30 min. We successfully identified variant TTRs in serum samples from patients, except for a few patients with TTR Glu61Lys and Glu89Gln mutations because of the small mass shift of those variant TTRs from wild-type TTR. We also found that the mass shifts of variant TTRs measured by direct MALDI corresponded to theoretical mass changes. Conclusion Our results suggest that the direct MALDI method is useful for the screening of ATTRv amyloidosis.